Adaptive Learning Strategies With Gamification To Enhance Learning Engagement - Mohamad, Siti Nurul Mahfuzah (Indian Society for Education and Environment, 2019)
Background/Objectives: In an adaptive learning strategy, the educator will decide what to teach manage and engage a student. Then, a student will get learning activities that suit their intelligence. Gamification is not an integral part of adaptive learning. However, adaptive learning using gamification can successfully organize to increase learning engagement. Methods/Statistical analysis: There are five phases involved in this study: (i) Determining Student Intelligence; (ii) Defining Learning Goal; (iii) Structuring Learner Experience; (iv) Analyze Suitable Game Elements and (v) Heutagogy Design Process. This study is designed for TVET students to collaborate, share the idea and discuss related issues to the context of the subject. This promotes critical thinking and communication skills among students. Participants involved in this study are undergraduate students from two TVET institutions in Malaysia. Findings: The findings demonstrate that students learn better and enhance students’ engagement. Activities in the class used real projects as an alternative assessment. Students won several awards. Improvements/Applications: Through e-Learning competition, give students opportunities to reflect their learning in order to help them develop critical thinking skills.